Unique profile of predominant CCR5-tropic in CRF07_BC HIV-1 infections and discovery of an unusual CXCR4-tropic strain - Hu, Xiaoyan; Feng, Yi; Li, Kang; Yu, Yueyang; Rashid, Abdur; Xing, Hui; Ruan, Yuhua; Lu, Lingling; Wei, Min; Shao, Yiming (Frontiers in Immunology, 2022)
CRF07_BC is one of the most prevalent HIV-1 strains in China, which contributes over one-third of the virus transmissions in the country. In general, CRF07_BC is associated with slower disease progression, while the underlying mechanisms remain unclear. Our study focused on envelope proteins (Env) and its V3 loop which determine viral binding to co-receptors during infection of cells. We studied a large dataset of 3,937 env sequences in China and found that CRF07_BC had a unique profile of predominantly single CCR5 tropism compared with CCR5 and CXCR4 dual tropisms in other HIV-1 subtypes. The percentages of the CXCR4-tropic virus in B (3.7%) and CRF01_AE (10.4%) infection are much higher than that of CRF07_BC (0.1%), which is supported by median false-positive rates (FPRs) of 69.8%, 25.5%, and 13.4% for CRF07_BC, B, and CRF01_AE respectively, with a cutoff FPR for CXCR4-tropic at 2%. In this study, we identified the first pure CXCR4-tropic virus from one CRF07_BC-infected patient with an extremely low CD4+T cell count (7 cells/mm3). Structural analysis found that the V3 region of this virus has the characteristic 7T and 25R and a substitution of conserved “GPGQ” crown motif for “GPGH”. This study provided compelling evidence that CRF07_BC has the ability to evolve into CXCR4 strains. Our study also lay down the groundwork for studies on tropism switch, which were commonly done for other HIV-1 subtypes, for the long-delayed CRF07_BC.